2021
DOI: 10.3390/su13094744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethnocentrism on Product Evaluation and Purchase Intention: The Case of Extra Virgin Olive Oil (EVOO)

Abstract: This study is framed within the concept of sustainability of local foods such as extra virgin olive oil (EVOO) and considers the effects of country of origin (COO) and ethnocentrism as relevant factors in decision making about product choice. Our work contributes to the literature regarding the food industry with the main objective of investigating how consumer ethnocentrism may affect not only behavioral intention but also the perception of the quality of the EVOO. The authors of the present paper developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 125 publications
3
15
0
1
Order By: Relevance
“…Our results confirmed that CET has a positive impact on consumers' purchasing intentions for national CRM products (hence confirming our first hypothesis). These results are in line with the positive bias of ethnocentric consumers towards national products, as suggested in previous CET studies, e.g., [59,61].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed that CET has a positive impact on consumers' purchasing intentions for national CRM products (hence confirming our first hypothesis). These results are in line with the positive bias of ethnocentric consumers towards national products, as suggested in previous CET studies, e.g., [59,61].…”
Section: Discussionsupporting
confidence: 92%
“…CET can be a major setback for brands trying to expand abroad [61]. As such, it has attracted attention from international marketing scholars who have examined it as a predictor of purchase intentions (PI), suggesting a negative bias of ethnocentric consumers towards international products [62] as well as a positive bias for domestic products [61]. However, CE is a more consistent predictor of domestic rather than foreign products [59].…”
Section: The Effects Of Cet and Perceived Economic Threat On Purchase Intentionsmentioning
confidence: 99%
“…Other studies explored local foods such as Spanish extra virgin olive oil and considered the effects of the country of origin (COO) and ethnocentrism as relevant factors in making a decision about product choice (e.g., the COO is considered an emotional dimension of purchasing behavior). The study suggested that understanding the role played by consumers' ethnocentrism in the evaluation of food products in accordance with their origin may yield useful information for local food producers [10]. Italian apples with PDO and PGI labels were compared to Italian apples without such labels [11] using chemical chemometrics and multielement composition analysis linked to soil and environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Pysarchik [ 41 ] found a statistically significant negative correlation between consumer ethnocentrism and a desire to buy domestic products [ 42 – 45 ]. Ethnocentrism in consumption can be analysed from many angles and products, and has been the subject of numerous studies and research [ 8 , 38 , 46 , 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%